The Influence of Host Country Pull Factors on Re-expatriation Intention among Academic Repatriates - Ramalu, Subramaniam Sri; Abdel-Rahman, Gheat Mahmoud Ali; Anuar, Amni (Migration Letters, 2023)
Unlike expatriation and repatriation, little is known about re-expatriation phenomenon especially the reasons why repatriates develop a re-expatriation intention after their return from abroad. Drawing on Push-Pull Theory, Theory of Family System and Expectancy Violation Theory, this study aims to examine the direct and indirect effects of host country pull factors (family outcomes and quality of life) on re-expatriation intention among Jordanian academic repatriates with the presence of psychological well-being as a mediating factor. In this quantitative research design, 153 Jordanian academic repatriates who had worked in foreign universities were surveyed using a snowball sampling technique. Partial least squares structural equation modelling (PLS-SEM) was used to test the proposed hypotheses of this study. The complementary mediation found in this study suggests that the relationship between host country pull factors and re-expatriation intention among Jordanian academic repatriates are both direct and indirect mediated though psychological well-being. The findings give rise to a number of implications, both theoretical and practical, in cross-cultural management research.